Reflux cholangitis in cholecysto- jejunostomy without performing a diverticular ansa.: Two cases - Beguiristain, Alberto; Lyonnet, Alberto; Lago, Fernando; Stein, Esther; Pombo, Gabriel; Praderi, Raúl (Cirugía del Uruguay, 1985)
Two cases of cholecysto-jejunostomy in which tactic and technical mistakes were done a long with their consequences are presented. lndication o! biliary-digestive anastomosis using gallbladder are discussed.